Analyis Of Digital Marketing Adoption Affected Buy Relative Advantage - Firdaus, Radit; Firdaus, Usep; Maulani, Galih Abdul Fatah; Hamdani, Nizar Alam (Jurnal Inovasi Bisnis dan Kewirausahaan, 2024)
Digital marketing adoption can be defined as the process of embracing and implementing sales strategies that prioritise the use of digital platforms and internet technology. This study is concerned with analysing the relative advantage of video marketing adoption on the TikTok platform in Indonesia, with a view to predicting its effectiveness. The population of this study consists of Indonesian individuals who use the TikTok platform. A sample of 420 respondents was selected via an online and face-to-face survey, with the objective of ensuring a random selection from the population. The data analysis technique employed in this quantitative research utilises a statistical approach. The programme employed for data analysis using the regression method is Statistical Product and Service Solution (SPSS). In order to meet the criteria for data analysis using regression, an interval scale is used. The data analysis technique employed in this study is regression. The findings of this study are highly precise, with a significance level of 95%. Drawing upon the findings of research analysis, digital marketing adaptation is influenced by relative advantage. The results indicate that the competitive industry refers to an economic sector where multiple companies must compete to promote similar goods or services on social media.